Penyuluhan Gizi Dan Pemeriksaan Kadar Hb Serta KEK Pada Remaja Putri Di Kecamatan Sukawati, Kabupaten Gianyar Tahun 2019 - Ida Ayu Eka Padmiari (Jurnal Pengabmas Masyarakat Sehat (JPMS), 2020)
Nutritional anemia generally occurs in women of reproductive age and children. This situation has the greatest overall effect in terms of health problems. Iron deficiency anemia is prone to occur in young women due to the increased need for iron during their infancy. The proportion of Chronic Energy Deficiency (KEK) in pregnant women in Sukawati District in 2017 was 34 mothers and in 2018 increased to as many as 40 pregnant women experiencing KEK, while the proportion of KEK in adolescent girls was not yet available. Likewise with the Proportion of Anemia in young women there is no data yet. Therefore, the servants will carry out Hb examination and measurement of LILA (Upper Arm Circumference) on young women in Sukawati sub-district, Gianyar Regency. The purpose of the Community Service is to provide counseling on nutrition, especially in the prevention of Anemia and KEK as well as examining hemoglobin levels in young women in Sukawati District, Gianyar Regency. The method used to achieve the objectives of community service is the method of lecture, discussion and examination of Hb levels and measurement of MUAC.Examination of hemoglobin levels was performed to determine the anemia status of the target. The average Hb level was 12.85 g / dl while the lowest value was 9.1 g / dl while the highest was 14.6 g / dl. Of the 50 targets examined found 14 targets (28%) anemia and 36 targets (72%) were not anemic. Determination of KEK status is done by measuring the target upper arm circumference (MUAC). Of the 50 targets measured there were 17 targets (34%) experienced KEK and 33 targets (66%) did not experience KEK. The conclusion of this community service counseling about Anemia and KEK in the prevention of anemia and KEK has succeeded in increasing good knowledge to be above 50%, Adolescent girls who have anemia by 28%, Adolescent girls who experience chronic Less Energy (KEK) by 34% in Sukawati District Gianyar RegencyKeywords: Anemia, Chronic Energy Deficiency, Adolescent Girls